Repurposing the Cord Blood Bank for Haplobanking of HLA‐Homozygous iPSCs and Their Usefulness to Multiple Populations. (29th July 2018) - Lee, Suji; Huh, Ji Young; Turner, David M.; Lee, Soohyeon; Robinson, James; Stein, Jeremy E.; Shim, Sung Han; Hong, Chang Pyo; Kang, Myung Seo; Nakagawa, Masato; Kaneko, Shin; Nakanishi, Mahito; et al.
Abstract: Although autologous induced pluripotent stem cells (iPSCs) can potentially be useful for treating patients without immune rejection, in reality it will be extremely expensive and labor‐intensive to make iPSCs to realize personalized medicine. An alternative approach is to make use of human leukocyte antigen (HLA) haplotype homozygous donors to provide HLA matched iPSC products to significant numbers of patients. To establish a haplobank of iPSCs, we repurposed the cord blood bank by screening ∼4, 200 high resolution HLA typed cord blood samples, and selected those homozygous for the 10 most frequent HLA‐A, ‐B, ‐DRB1 haplotypes in the Korean population. Following the generation of 10 iPSC lines, we conducted a comprehensive characterization, including morphology, expression of pluripotent markers and cell surface antigens, three‐germ layer formation, vector clearance, mycoplasma/microbiological/viral contamination, endotoxin, and short tandem repeat (STR) assays. Various genomic analyses using microarray and comparative genomic hybridization (aCGH)‐based single nucleotide polymorphism (SNP) and copy number variation (CNV) were also conducted. These 10 HLA‐homozygous iPSC lines match 41.07% of the Korean population. Comparative analysis of HLA population data shows that they are also of use in other Asian populations, such as Japan, with some limited utility in ethnically diverse populations, such as the UK. Taken together, the generation of the 10 most frequent Korean HLA‐homozygous iPSC lines serves as a useful pointer for the development of optimal methods for iPSC generation and quality control and indicates the benefits and limitations of collaborative HLA driven selection of donors for future stocking of worldwide iPSC haplobanks.Stem Cells 2018;36:1552–1566 Abstract : By repurposing the existing cord blood bank, we established 10 most frequent HLA‐homozygous iPSC lines from the Korean population. Comparative HLA analysis indicates that they are relevant to multiple populations including Japan and the UK. This study highlights the importance of collaborative HLA driven selection of donors for future stocking of worldwide iPSC haplobanks.